SHINESeniors: Personalized Services for Active Ageing-in-Place - BAI, Liming (Institutional Knowledge at Singapore Management University, 2015)
Singapore faces a major challenge in providing care and support for senior citizens due to its rapidlyageing population and declining old-age support ratio. The concept of Ageing-in-Place was introduced by the Singapore government [1] to allow older people to live independently in their own homes and communities so that the need for institutionalised care will only be utilised when necessary. We have three fundamental questions that this project will answer: 1. How to make community care serviceseffective through innovations in care delivery? How to lower the cost of service delivery and improve 2. productivity of caregivers, by leveraging information and communications technology (ICT)? 3. Can we quantify such productivity gains?